Assessing Older Adults' Masticatory Efficiency. Issue 6 (June 2015) - Cusson, Valérie; Caron, Christian; Gaudreau, Pierrette; Morais, José A.; Shatenstein, Bryna; Payette, Hélène
<x xml:space="preserve">Abstract</x> Objectives To determine internal consistency and criterion validity of a questionnaire assessing perception of masticatory efficiency in community‐dwelling older adults. Design Secondary cross‐sectional analysis of baseline data from the Québec Longitudinal Study on Nutrition and Successful Aging (NuAge). Setting NuAge is a 5‐year (2003–08) observational study of 1, 793 men and women aged 67 to 84 in good general health at recruitment. Participants A sample of 1, 789 was used to determine internal consistency of the questionnaire. A subsample (n = 94) of the cohort who underwent a clinical test directly measuring masticatory efficiency was used to determine criterion validity of the questionnaire. Measurements The questionnaire was a subset of the Oral Health Impact Profile containing 7 Likert‐scale questions (score 0–28 points). Masticatory efficiency was assessed using a validated clinical test measuring ability to chew a raw carrot (Swallowing Threshold Test Index, score 0–100%). For perceived and measured data, a higher score indicated better masticatory efficiency. Results Internal consistency of the questionnaire was deemed good (Cronbach alpha = 0.803). Mean scores were generally high (men, 25.3, 95% confidence interval (CI) = 24.7–25.9; women, 24.3, 95% CI = 23.7–25.0), indicating good perceived masticatory efficiency for men and women. Mean performance test scores were low (men, 60.8%, 95% CI = 57.3–64.2; women, 61.2%, 95% CI = 57.7–64.7). No significant relationship between perceived and measured masticatory efficiency was observed (Pearson correlation coefficient = −0.14, P = .22). Conclusion Despite good internal consistency of the questionnaire and the recognized validity of the test, people's perception of their masticatory efficiency does not reflect objective efficiency as measured using a clinical test.